Clinical characteristics and treatment outcome of acute myeloid leukemia in elderly patients in Korea: a retrospective analysis - Yi, Hyeon Gyu (Korean Society of Hematology; Korean Society of Blood and Marrow Transplantation; Korean Society of Pediatric Hematology-Oncology; Korean Society on Thrombosis and Hemostasis, 2014)
BACKGROUND: The clinical characteristics of elderly patients with AML differ from those of younger patients, resulting in poorer survival and treatment outcomes. We analyzed retrospectively the clinical data of AML patients 65 years old and above to describe patients' characteristics and treatment patterns, and to define meaningful prognostic factors of survival in the Korean population. METHODS: Basic patients' characteristics, clinical outcomes according to treatments, and prognostic factors associated with survival and treatment intensity were examined in a total of 168 patients diagnosed in 5 institutes between 1996 and 2012 as having AML. RESULTS: Herein, 84 patients (50.0%) received high-intensity regimens (HIR), 18 (10.7%) received low-intensity regimens (LIR), and 66 (39.3%) received supportive care (SC) only. The median survival of all patients was 4.5 months; and median survival times with HIR, LIR, and SC were 6.8 months, 10.2 months, and 1.6 months, respectively. Median survival times with HIR and LIR were significantly longer than that with SC (P<0.0001 and P=0.006, respectively). Multivariate analysis identified age, Eastern Cooperative Oncology Group-performance status (ECOG-PS), hemoglobin (Hb) level, and serum creatinine (Cr) level as statistically significant prognostic factors for survival. In the HIR group, prognostic factors for survival were ECOG-PS, Hb level, and C-reactive protein level. CONCLUSION: Even in elderly AML patients, an intensive treatment regimen could be beneficial with careful patient selection. Further prospective studies designed to identify specific prognostic factors are required to establish an optimal treatment strategy for elderly AML patients.